2014
DOI: 10.1161/strokeaha.113.003744
|View full text |Cite
|
Sign up to set email alerts
|

Role of Preexisting Disability in Patients Treated With Intravenous Thrombolysis for Ischemic Stroke

Abstract: Background and Purpose— Little is known about the effect of thrombolysis in patients with preexisting disability. Our aim was to evaluate the impact of different levels of prestroke disability on patients’ profile and outcome after intravenous thrombolysis. Methods— We analyzed the data of all stroke patients admitted between October 2003 and December 2011 that were contributed to the Safe Implementation of Treatments in Stroke–Eastern Europe (SITS-EAST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 20 publications
7
57
0
Order By: Relevance
“…This observation is unpreceded and differed from the result of a subgroup analysis in another study, suggesting a higher risk of poor outcome in patients with preexisting dependency (OR adjusted , 1.70; 0.99-2.94). 12 Unexpectedly, among survivors, previously dependent patients had better odds to avoid poor outcome than independent patients in our cohort if age and stroke severity were taken into account. We can only speculate on possible reasons: (1) our definition of poor outcome (which we adopted from a previous study 12 ) differed between both groups and may have favored the previously dependent patients.…”
Section: February 2016mentioning
confidence: 70%
See 3 more Smart Citations
“…This observation is unpreceded and differed from the result of a subgroup analysis in another study, suggesting a higher risk of poor outcome in patients with preexisting dependency (OR adjusted , 1.70; 0.99-2.94). 12 Unexpectedly, among survivors, previously dependent patients had better odds to avoid poor outcome than independent patients in our cohort if age and stroke severity were taken into account. We can only speculate on possible reasons: (1) our definition of poor outcome (which we adopted from a previous study 12 ) differed between both groups and may have favored the previously dependent patients.…”
Section: February 2016mentioning
confidence: 70%
“…12 Unexpectedly, among survivors, previously dependent patients had better odds to avoid poor outcome than independent patients in our cohort if age and stroke severity were taken into account. We can only speculate on possible reasons: (1) our definition of poor outcome (which we adopted from a previous study 12 ) differed between both groups and may have favored the previously dependent patients. In detail, among survivors, dependent patients with a prestroke mRS score of 3 can only move to an mRS score of 4 or 5, patients with a GFR indicates glomerular filtration rate; mRS, modified Rankin Scale; NIHSS, National Institutes of Health Stroke Scale; poor outcome, not reaching at least prestroke mRS in previously dependent patients (mRS score of 3 to 6 in previously independent patients); prestroke completely dependent, prestroke mRS score of 4 to 5; prestroke dependent, prestroke mRS score of 3 to 5; prestroke independent, prestroke mRS score of 0 to 2; prestroke partially dependent, prestroke mRS score of 3; and sICH, symptomatic intracranial hemorrhage (European Cooperative Acute Stroke Study [ECASS] II definition).…”
Section: February 2016mentioning
confidence: 70%
See 2 more Smart Citations
“…Research has explored whether or not pre-stroke disability was associated with negative outcomes of thrombolysis. 44 It was concluded that pre-stroke disability does not independently increase the risk of sICH after thrombolysis. However, higher modified Rankin Scale (mRS) scores (high scores indicating greater dependency on others for assistance with daily living) were associated with an increased risk of death at 3 months post treatment.…”
Section: Patient-related Factors That Can Influence Clinician Decisiomentioning
confidence: 99%